An improved smooth shift strategy for clutch mechanism of heavy tractor semi-trailer automatic transmission. (April 2022) - Ouyang, Tiancheng; Lu, Yucai; Li, Shuoyu; Yang, Rui; Xu, Peihang; Chen, Nan
Abstract: The shift quality of an automatic transmission (AT) has a significant impact on the driving comfort, fuel economy and service life of heavy tractor semi-trailer. Existing research on shift control in such vehicles is scarce and improved shift quality can contribute to development of the transportation industry. In this study, a shift strategy using a robust tracking control algorithm for AT heavy tractor semi-trailers is proposed. A high-order dynamic model with clutch actuator and planetary gear is proposed for the heavy tractor semi-trailers. Based on the clutch slip speed, a robust control strategy consisting of feedforward, feedback, and disturbance controllers is designed to provide precise control and quick response of shift actuator. Experimental data is compared with the numerical results to validate the reliability of shift control strategy. Besides, this study analyses the influence of hitch articulation angle and steering angle of semi-trailer on disturbance torque and verifies the efficacy of the proposed controller by comparing its performance to those of a traditional proportion integral differential controller and an adaptive control method. Results show that the proposed controller is superior to the traditional controller considering the tracking error, shift time, friction work, and significantly improves shift quality. Graphical abstract: Highlights: A dynamic model is proposed for heavy tractor semi-trailer automatic transmission. Friction coefficient of clutch is fitted using elastohydrodynamic simulation. A robust controller considering uncertain dynamics is put forward. Effects of hitch articulation and steering angles on resistance torque are studied.